2019
DOI: 10.1177/0004867419857821
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the paradox of increased mental health expenditure and stable prevalence

Abstract: A doubling of Australian expenditure on mental health services over two decades, inflation-adjusted, has reduced prevalence of neither psychological distress nor mental disorders. Low rates of help-seeking, and inadequate and inequitable delivery of effective care may explain this partially, but not fully. Focusing on depressive disorders, drawing initially on ideas from the work of philosopher and socio-cultural critic Ivan Illich, we use evidence-based medicine statistics and simulation modelling approaches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 17 publications
1
28
1
Order By: Relevance
“…Response rates (symptom reduction of 50% or more from baseline) in aADM arms exceed those in PLA arms, typically by 10-15%. The largest recent meta-analysis of aAD efficacy by Cipriani et al included 522 trials, published and unpublished, comprising 1 16 477 participants and found that ADs had better response rates than placebo, with ORs ranging between 1.37 and 2.13 and an averaged SMD = 0.30, similar to NNT = 8 (Meadows et al, 2019), comparable with other recent meta-analyses (Cipriani et al, 2018). Although treatment settings were often unclear, most trials did not take place in primary care settings.…”
Section: Factors That Keep Fueling the Disputementioning
confidence: 99%
“…Response rates (symptom reduction of 50% or more from baseline) in aADM arms exceed those in PLA arms, typically by 10-15%. The largest recent meta-analysis of aAD efficacy by Cipriani et al included 522 trials, published and unpublished, comprising 1 16 477 participants and found that ADs had better response rates than placebo, with ORs ranging between 1.37 and 2.13 and an averaged SMD = 0.30, similar to NNT = 8 (Meadows et al, 2019), comparable with other recent meta-analyses (Cipriani et al, 2018). Although treatment settings were often unclear, most trials did not take place in primary care settings.…”
Section: Factors That Keep Fueling the Disputementioning
confidence: 99%
“…Loss of Agency refers to loss of self-efficacy, problem solving, and other self-help activities that normally benefit recovery [9]. Without treatment, depressed people often engage independently in selfhelp strategies, such as exercising, increasing pleasant activities, reducing stress, and meditation [15].…”
Section: Loss Of Agency and Self-help Activitiesmentioning
confidence: 99%
“…Nowadays, more than 80% of Selective Serotonin Reuptake Inhibitor (SSRI) prescriptions are written by General practitioners (GP)s, who may have fewer empowering strategies in their armamentarium or time to implement those. People in disadvantaged communities might thus be deprived twice over because they tend to receive more AD-monotherapy and less rigorous PT treatment compared to the more comprehensive service delivery of combined AD and empowering psychotherapy in affluent areas [9].…”
Section: Loss Of Agency and Self-help Activitiesmentioning
confidence: 99%
“…The target group for specialist mental health services is an estimated 3% of the population, concordant with overall population prevalence of VHK-10 scores at 3.6% [6]. While many factors influence psychological distress, the composite SED construct includes many powerful influences on these rates [11] and so has a strong claim to be included in bed distribution [9] and other resource considerations.…”
Section: Key Pointsmentioning
confidence: 99%